Review of Edgar Schuster’s Breaking the Rules: Liberating Writers Through Innovative Grammar Instruction (2003) - Bani-Khair, Baker Mohammad Jamil; Alkhalifah, Ziyad khalifah (Technium Social Sciences Journal, 2023)
Breaking the Rules: Liberating Writers Through Innovative Grammar Instruction (2003) is a book on teaching English Grammar, composition, and practicing language rules efficiently in a more independent and individualistic sense away from old approaches of Grammar- Translation Method that have been used since ages. Edgar Schuster is a well-known author for his great interest in studying and exploring English Grammar and mastering structures. He is also known for his influential and important works that contributed much to educational development and innovation. He has published several articles and textbooks related to Grammar instruction, language planning, and writing and composition. Schuster has a broad and long experience in teaching English in secondary schools and colleges for more than forty years, and has won many awards for his distinguished teaching and research. He has been a master teacher at Harvard university, and an author of many important and significant books On Grammar and sentence structure, such as Sentence Mastery: A Sentence-Combing Approach Level B, (1989), Grammar: Usage and Style (1965), American English Today: The tools of English (1977), and many other significant books including the name of this book reviewed in this paper.